The Impact of Work-Life Balance and Employee Engagement on Performance Mediated by Digitalization - Jamiyati, Ani; Bagusromadhan, Trisno Ajisantoso; Alvarezy, Ryan; Yahya, Adibah; Wiyatno, Tri Ngudi (LPPPIPublishing, 2025)
This study aims to analyze the influence of Human Resource Management (HRM), Work-Life Balance (WLB), and employee involvement on employee performance, with digitalisation as a mediating variable. The digital era has transformed the paradigm of HR management, requiring organisations to become more adaptive to technological developments. This research was conducted at PT XYZ, Bekasi Regency, using a quantitative approach with purposive sampling involving 148 respondents. The findings show that HRM and employee involvement do not have a direct impact on employee performance, while WLB has a positive and significant effect. Moreover, digitalisation significantly mediates the relationship between the three independent variables and employee performance. These results highlight the importance for organisations to prioritise work-life balance policies and integrate digital technologies into HR practices such as performance appraisal systems, employee training programs, and digital communication platforms—to enhance employee performance. This study contributes to the theoretical development of HRM in the digital age and provides practical implications for strategic decision-making in human resource management.